The Role and Current Status of IFRS in the Completion of National Accounting Rules – Evidence from European Countries. (4th May 2017) - André, Paul
Abstract: I present a summary and analysis of a series of papers from this special issue of Accounting in Europe that examine the role and current status of International Financial Reporting Standard (IFRS) in the completion of National Accounting Rules applicable to large 'non-listed in a regulated market' non-financial undertakings trading for gain in 25 European countries following the recent implementation of the new European Accounting Directive 2013/34/EU. IFRS has had a varying degree of influence across European countries. Some refer and are closely aligned to IFRS or to IFRS for small and medium-sized entities, some while influenced by IFRS retain complete independence and some show limited influence mostly when accounts are for other purposes such as taxation, dividend distribution or creditor protection. I present a number of classification schemes and contrast these with Nobes [(2008). Accounting classification in the IFRS Era. Australian Accounting Review, 18 (3), 191–198] two group accounting classification of European accounting systems as strong equity/commercially driven versus weak equity/government driven/tax-dominated systems.